Phosphorus transformation behavior and phosphorus cycling genes expression in food waste composting with hydroxyapatite enhanced by phosphate-solubilizing bacteria. (May 2023) - Xu, Shaoqi; Jia, Kaixue; Zheng, Yi; Chen, Wenjie; Wang, Zhigang; Wei, Dan; Sun, Baoru; Cheng, Meidi; Fan, Beibei; Li, Ji; Wei, Yuquan
Graphical abstract: PSB inoculation increase 8.1% AP content and decrease Po/Pi ratio in FW composting. Highlights: Inoculation in the cooling stage promote the dissolution of hydroxyapatite. Inoculation decreased bacterial diversity but enhanced Bacillus relative abundance. PSB inoculation led bacterial community genera from "generalists" to "experts". Genes of Pi-solubilizing in Bacillus and Po-mineralization in others were enhanced. Abstract: This study aimed to explore the effect of phosphate-solubilizing bacteria (PSB) Bacillus inoculation in the cooling stage on hydroxyapatite dissolution, phosphorus (P) forms transformation, and bacterial P cycling genes in food waste composting with hydroxyapatite. Results indicated that PSB inoculation promoted the dissolution of hydroxyapatite, increased P availability of compost by 8.1% and decreased the ratio of organic P to inorganic P by 10.2% based on sequential fractionation and 31 P nuclear magnetic resonance spectroscopy. Illumina sequencing indicated Bacillus relative abundance after inoculation increased up to one time higher than control after the cooling stage. Network analysis and metabolic function of bacterial community analysis suggested inorganic P solubilizing genes of Bacillus and organic P mineralization genes of other genera were improved after inoculation in the core module. Therefore, bioaugmentation of PSB in the cooling stage may be a potential way to improve P bioavailability of bone and food waste in composting.